A Stability Assessment of Fault-Caprock Trapping Systems for CO2 Storage in Saline Aquifer Layers Using a Coupled THMC Model - Mingying Xie; Shenghao Wang; Shasha Feng; Chao Xu; Xisheng Li; Xiaona Sun; Yueqiang Ma; Quan Gan; Tao Wang (Energies, 2025)
Deep saline aquifers provide significant potential for CO2 storage and are crucial in carbon capture, utilization, and storage (CCUS). However, ensuring the long-term safe storage of CO2 remains challenging due to the complexity of coupled thermal, hydrological, mechanical, and chemical (THMC) processes. This study is one of a few to incorporate fault-controlled reservoir structures in the Enping 15-1 oilfield to simulate the performance of CO2 geological storage. A systematic analysis of factors influencing CO2 storage safety, such as the trap area, aquifer layer thickness, caprock thickness, reservoir permeability, and reservoir porosity, was conducted. We identified the parameters with the most significant impact on storage performance and provided suitable values to enhance storage safety. The results show that a large trap area and aquifer thickness are critical for site selection. Low permeability and large caprock thickness prevent CO2 from escaping, which is important for long-term and stable storage. These findings contribute to developing site-specific guidelines for CO2 storage in faulted reservoirs.